Síntese e otimização econômica de um sistema energético em um hotel paraibano - Lima, Karollyne Marques de (2021)
Polygeneration systems, also known as combined power generation, in which two or more energy services are obtained from a single resource, assisted by renewable energy sources are considered important alternatives to supply the energy demands of buildings. However, determining the best configuration and operational strategy for these types of systems is a complex task, due to the multiple technology options available and the dynamic operating conditions of buildings and their surroundings. This work deals with the synthesis and optimization of an energy system for a commercial building (hotel). Demand for electricity, hot water and refrigeration was considered for a hotel located in Conde, in the state of Paraíba. The optimization problem was based on Mixed Integer Linear Programming, and included conventional equipment and solar energy (photovoltaic and thermal) and biomass. The objective function of the optimization was to minimize annual economic costs, which considered equipment and operating costs. The model solution suggested the installation of 70 photovoltaic panels, and used biomass (sugarcane bagasse) to start a boiler for the production of hot water. Solar collectors for hot water production were not part of the solution. For comparison purposes, a reference system was established, where energy demands are met in a conventional manner (without cogeneration or renewable energy), whose annual cost was R$ 80.799,00. Although with an initial investment of higher equipment for the optimized system, it benefited from the high degree of energy integration and had a total annual cost of R$ 24.358,00 (30,2% lower). Sensitivity analyzes were evaluated, varying the tariff modality, the natural gas tariff, the type of biomass, and the electricity tariff. The economical solution indicated an energy system using renewable resources, biomass and photovoltaic solar energy, to minimize the total annual costs of the hotel's energy supply.